Online Platforms in Mobile Learning as Online Learning Media during the COVID-19 Pandemic - Fella Farikhatus Sholikhah; Triana Rejekiningsih; Leo Agung Sutimin (Teknodika, 2022)
This paper aims to describe platforms in mobile learning during the pandemic. This writing was motivated by an uncontrolled pandemic that made several aspects uncontrollable, including education, so learning activities were forced to change. Therefore, there is a need to update learning through learning media with several platforms available for mobile learning. This online platform in mobile learning is a medium that can solve students' problems during a pandemic that helps the learning process run. The method used in this paper was to use a literature study that examined several sources of articles from research results published to be analyzed and draw conclusions. This paper indicated that platforms such as Google Classroom, Zoom, and Microsoft Teams could solve problems during the pandemic. The average result was more than 60% based on the data presented. This figure is considered to have reached the effective criteria. Learning using online platforms, such as Google Classroom, Zoom, and Microsoft Teams, can be an alternative and help activate students when offline learning cannot be carried out, even mobile-based learning media.